Cancer genetics and psychotherapy - Mehdipour, Parvin (Springer, 2017)
Cancer is the scandal magic event of Nature. Psycho-Oncogenetic is an insight for research, education, and translated cancer medicine that open a new window to patients, psychologists, surgeons, oncologists, haematologists, geneticists and scientists who are aimed to pave the ways towards an alternative management for cancer patients. Being cooperative, innovative, perceptive, and inspired are some essential characteristics for, participating in cancer translated research. Applicability of suggestive complementary insights including Pharmacogenomics (PG), Pharmacokinetics (PK), Pharmaco-Psycho-Somatic (PPS), Pharmaco-Psycho-Genomics (PPG), Pharmaco-Psycho-Kinetics (PPK), may facilitate the access of the Personalized Pharmaco-Therapy (PPT) as the reliable target-based strategy. So, by bridging Pharmacogenetics to Psycho-Genetics, the harmonized and multi- target-based insights would, gradually, facilitate to connect the initial station of cancer coach to the final station of cancer management, which is the appropriate individualized cancer therapy. In this regards, the global insight is required to be replaced by the personalized cascade management from A to Z. It was my task and aim to consider a comprehensive manner in editing of this book. This endeavor was relied on the authors and co-authors who have, greatly, contributed to this package which will, hopefully, spread the provided basic and applicable scientific, and clinical messages to the audiences who play roles in the cancer world. The contents of this book include 26 chapters including basic Science/Genetics, psychology and clinical aspects in different tumors. The contents of this package may inspire a profounder concern of coordinated strategy in cancer research and cancer management. Besides, it may also provide some clues to positioning of puzzles for innovating the target-based cancer therapy. Let's move towards planning an appropriate social life style with an individualized diagnosis and management for cancer patients. By considering the global sharing, triggering the burdens is the key aim in cancer.
Keywords: Cancer -- Genetic aspects.; Cancer -- Patients -- Psychology.; elektronické knihy; electronic books